2011
DOI: 10.1016/j.biortech.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel saccharification method of starch using microwave irradiation with addition of activated carbon

Abstract: Activated carbons were investigated for their heat catalytic effects to improve saccharification of starch by autohydrolysis in water under microwave electromagnetic field, and the results were compared with graphite and carbon nanotubes. The activated carbons with low adsorptive capacity of maltose showed high saccharification rate, while those with high adsorptive capacity exhibited low saccharification. In addition, the former activated carbons decreased the saccharification temperature by 10-30°C. Maltooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…21–23. The process of microwave‐assisted starch hydrolysis has also been investigated 24, 25. Up to now there is no information on employing microwaves in starch oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…21–23. The process of microwave‐assisted starch hydrolysis has also been investigated 24, 25. Up to now there is no information on employing microwaves in starch oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Matsumoto et al (2011) and Khan et al (1979) reported that microwave treatment can be an alternative method for starch hydrolysis in water; Warrand and Janssen (2007) and Yu et al (1996) stated that starch in acid hydrolysis can produce oligosaccharide. Some researchers also reported the microwave-assisted hydrolysis can be applied to the mixture of starch and fiber from industrial waste such as cassava pulp (Hermiati et al 2011) and waste from the corn starch industry (Yoshida et al 2010).…”
Section: Effect Of Microwave-assisted Hydrolysis In Dilute Acidmentioning
confidence: 99%
“…Therefore, it was considered as energy efficient approach for biomass pretreatment under low pressure and temperature [14,15], and the microwave heating even improved the glucose selectivity [16]. Previously, it was reported that microwave treatment for saccharification in water and acid hydrolysis can produce oligosaccharides [17,18].…”
Section: Introductionmentioning
confidence: 99%